Immunocytochemical and Morphometric Studies of Gastrin-, Somatostatin- and Serotonin-Producing Cells in the Stomach and Duodenum of Patients with Acid Peptic Disorders. (1st October 1996) - Yacoub, WR; Thomson, ABR; Hooper, P; Jewell, LD
Abstract : Gastric and duodenal biopsies from 90 patients with various acid peptic disorders - reflux esophagitis (n=24), gastric ulcer (n=13), duodenal ulcer (n=47) and nonulcer dyspepsia (n=6) - were examined. Seven patients with minimal dyspeptic symptoms and an endoscopically and histologically normal stomach and duodenum served as controls. Immunoperoxidase staining for gastrin-producing G cells, somatostatin-producing D cells and serotonin-producing EC cells was carried out on fundic, antral and duodenal biopsies, and was quantified using a Zeiss MOP Videoplan using the peroxidase-antiperoxidase technique of Sternberger. In the gastric antrum, a G:D:EC cell ratio of approximately 1.6:1:1 was observed. In the duodenum the corresponding ratio was 1:1:2.4. No significant differences were observed within any of the major diagnostic categories. Patient age, sex, duration of symptoms, smoking habits, alcohol consumption and nonsteroidal anti-inflammatory drug use had no effect on endocrine cell densities. Reduced G cell density in the descending duodenum was observed in the presence of mild duodenitis in four patients. In four patients with evidence of antral intestinal metaplastic changes, a significant increase in duodenal G cell densities was found. These results suggest that a change in the number of G, D or EC cells does not play a primary role in the pathophysiology of acid peptic disorders in the majority of patients.